Migrant Remittances and the Investment Climate: Exploring the Nexus - Sander, Cerstin (Washington, DC: World Bank, 2012)
Migrant remittances are the second largest source of private capital flows into developing countries after FDI. Remittance flows augment foreign exchange reserves, strengthen the deposit base, and improve country credit ratings. Although migration may result in a brain drain, these flows and the capital and human skills of migrant returnees contribute to investment and wealth creation. Remittances can be facilitated by improving financial infrastructure and systems which will also enhance the investment climate.